Spontaneous platelet aggregation (SPA) predicts pre-eclampsia and intra-uterine growth restriction. (18th April 2012) - Burke, N; Murray, A; Dunne, E; Dicker, P; Dempsey, M; O'Connor, H; Fonseca-Kelly, Z; Cotter, B; Geary, M; Flood, K; Kenny, D; Malone, F
Abstract : Platelet function has not been well characterised in pregnancy. We used a modification of light transmission aggregometry to prospectively assess SPA in normal and complicated pregnancies. The study was powered (80%) to detect a 6% change in platelet aggregation across the time-points and an 8% change for PET or IUGR. In 50 patients with normal pregnancy, platelet function was assessed in the three trimesters and post-natally. In 35 patients with pre-eclampsia (PET) and 18 patients with intra-uterine growth restriction (IUGR) platelet function was assessed in the third trimester. Comparisons between platelet function assays in the four time points of normal pregnancy were made using a mixed effects model with study participant as a random-effect, allowing for possible correlations between the repeated assessments. ANOVA was used to compare these assessments with the PET and IUGR groups. The results are presented as Bonferroni adjusted p-values. SPA increased significantly between the 1st and 2nd trimester (7% increase, p-value=0.0001); the 3rd trimester (9% increase, p-value=0.0020) and the post-natal assessment (15% increase, p-value=0.0002) in normal pregnancy. In contrast there was no increase in the platelet aggregation profile of patients with either PET or IUGR. We demonstrate for the first time a significant incremental increase in SPA with advancing gestational age in normal pregnancy. In contrast this increase in platelet aggregation does not occur in the third trimester in platelets from patients with either PET or IUGR. These results suggest that sequential analysis of SPA may be a novel marker for at risk pregnancies.